2021
DOI: 10.3389/fpls.2021.680151
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Resistant and Susceptible Responses in a New Model Root-Knot Nematode Infection System Using Solanum torvum and Meloidogyne arenaria

Abstract: Root-knot nematodes (RKNs) are among the most devastating pests in agriculture. Solanum torvum Sw. (Turkey berry) has been used as a rootstock for eggplant (aubergine) cultivation because of its resistance to RKNs, including Meloidogyne incognita and M. arenaria. We previously found that a pathotype of M. arenaria, A2-J, is able to infect and propagate in S. torvum. In vitro infection assays showed that S. torvum induced the accumulation of brown pigments during avirulent pathotype A2-O infection, but not duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 153 publications
(175 reference statements)
1
5
0
Order By: Relevance
“…The major proteins annotated to defense response, response to oxidative stress, and lipid oxidation processes were peroxidases, alpha-dioxygenase, allene oxide synthesis, lipoxygenase, and benzoate O-methyltransferase (Supplementary Tables S3 and S4). Interestingly, the expression of genes encoding class III peroxidases was induced at 24 hpi, followed by the induction of the expression of genes involved in defense response at 3 dpi during compatible interactions between M. arenaria and S. torvum (Sato et al 2021), which partially overlaps with results observed in this study. On the other hand, we previously reported downregulation of gene encoding peroxidase in all analyzed time points (24 hpi, 3 dpi, and 7 dpi) in maize response to M. arenaria infection.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The major proteins annotated to defense response, response to oxidative stress, and lipid oxidation processes were peroxidases, alpha-dioxygenase, allene oxide synthesis, lipoxygenase, and benzoate O-methyltransferase (Supplementary Tables S3 and S4). Interestingly, the expression of genes encoding class III peroxidases was induced at 24 hpi, followed by the induction of the expression of genes involved in defense response at 3 dpi during compatible interactions between M. arenaria and S. torvum (Sato et al 2021), which partially overlaps with results observed in this study. On the other hand, we previously reported downregulation of gene encoding peroxidase in all analyzed time points (24 hpi, 3 dpi, and 7 dpi) in maize response to M. arenaria infection.…”
Section: Discussionsupporting
confidence: 87%
“…incognita infection (Shukla et al 2018). Induction of genes related to cell wall modifications was also observed during Solanum torvum's response to M. arenaria infection (Sato et al 2021). These data overlap with results described in this study, where changes in the accumulation level of proteins related to cell wall modifications were observed at both time points.…”
Section: Discussionmentioning
confidence: 90%
“…Another study suggested that physical reinforcement of cell walls with lignin is an important defense response against nematodes. The Solanum torvum-root-knot nematode system can provide a molecular basis for understanding plant-nematode interactions [40]. In S. torvum, a resistant root stock for eggplant and root-knot nematode interactions, infestation by an avirulent pathotype of Meloidogyne arenaria induced the expression of several genes such as class III peroxidases, fatty acid desaturases, sesquiterpene synthases, and genes involved in defense, hormone signaling, biosynthesis of lignin, etc., which contribute to resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a good number of resistant genotypes, an urgent need is apparent for more ones to reduce PPN losses. Moreover, the majority of plant resistance genes used are effective against only the above-mentioned sedentary nematode category [30,33,42]. Hence, introgression of R-genes to confer nematode resistance to susceptible plants via classical genetic breeding can offer potent steps change in crop productivity [43][44][45].…”
Section: Successes and Difficulties In Using R-genesmentioning
confidence: 99%